(untitled) (Research, Society and Development, 2020)
Pandemics are events of a collective nature whose main characteristic is the manifestation of an infectious disease, highly transmissible and with great lethality. The clinical spectrum of Covid-19 infection appears to be broad, ranging from asymptomatic infection, or slight changes in the respiratory tract with the presence of rhinorrhea, sneezing, sore throat and cough, to more severe cases of viral pneumonia. The objective was to conduct a reflection on the mental health conditions of nursing teams working in urgent and emergency sectors in the context of the Covid-19 pandemic. As well as, promote through discussion, strategies that can be used in order to prevent psychological damage in these employees. A bibliographic survey was carried out through an exploratory search for scientific productions in the Virtual Health Library (VHL) directed to the following databases: Scientific Eletronic Library Online (Scielo), Latin American and Caribbean Literature in Life Sciences. Health (Lilacs) and International Health Sciences Literature (Medline). In addition, theses and dissertations that had related themes were also used, in addition to guiding protocols as mentioned previously. With this, points were built for reflective discussion based on guiding axes regarding the initial experience with the pandemic, the routine and alternatives of mental health care. The related reflection can raise important points that deserve attention about the mental health care of the nursing team that works directly in the urgent and emergency sectors during this pandemic period.